Favourable outcomes of poor prognosis diffuse large B‐cell lymphoma patients treated with dose‐dense Rituximab, high‐dose Methotrexate and six cycles of CHOP‐14 compared to first‐line autologous transplantation. (23rd June 2017) - Strüßmann, Tim; Fritsch, Kristina; Baumgarten, Axel; Fietz, Thomas; Engelhardt, Monika; Mertelsmann, Roland; Ihorst, Gabriele; Duyster, Justus; Finke, Jürgen; Marks, Reinhard
Summary: The optimal therapeutic approach for young diffuse large B‐cell lymphoma (DLBCL) patients with high‐intermediate and high‐risk age‐adjusted international prognostic index (aaIPI) remains unknown. Hereby we report a 10‐year single‐centre study of 63 consecutively treated patients. To optimize outcome, two approaches were carried out: Cohort 1 patients received four cycles R‐CHOP‐21 (rituximab, cyclophosphamide, daunorubicin, vincristine, prednisolone over 21 days) followed by first‐line high‐dose chemotherapy with autologous stem‐cell support (HDCT‐ASCT), resulting in 2‐year progression‐free (PFS) and overall survival (OS) of 60·6% and 67·9%. 39·4% of those patients were not transplanted upfront, mainly due to early progressive disease (24·2%). Cohort 2 patients received an early intensified protocol of six cycles of CHOP‐14 (cyclophosphamide, daunorubicin, vincristine, prednisolone over 14 days) with dose‐dense rituximab and high‐dose methotrexate resulting in promising overall response‐ (93·3%) and complete remission (90%) rates and sustained survival (2‐year PFS and OS: 93·3%). In an intention‐to‐treat analysis, 2‐year PFS (60·6% vs. 93·3%, hazard ratio [HR] 7·2, P = 0·009) and OS (69·7% vs. 93·3%, HR 4·95, P = 0·038) differed significantly, in favour of the early intensified protocol (Cohort 2). In a multivariate Cox‐regression model, PFS (HR 8·12, 95% confidence interval [CI] 1·83–35·9, P = 0·006) and OS (HR 5·86, 95% CI 1·28–26·8, P = 0·02) remained superior for Cohort 2 when adjusted for aaIPI3 as the most important prognostic factor. Survival of young poor‐prognosis DLBCL patients appears superior after early therapy intensification.